Mean Field Equations for the Equilibrium Turbulence and Toda Systems on Connected Finite Graphs (Journal of Partial Differential Equations, 2022)
In this paper, we study existence of solutions of mean field equations for the equilibrium turbulence and Toda systems on connected finite graphs. Our method is based on calculus of variations, which was built on connected finite graphs by Grigor'yan, Lin and Yang.
Keywords: Mean field equation; equilibrium turbulence; Toda system; finite graph.